“But Here Comes the Water…” —Dam-Induced Displacement and Resettlement in the Technological and Hydroelectric Landscapes of Portugal’s New State (1933–1974) - Pereira André (HoST)
This ongoing research considers the submersion of villages by dams during the construction of the Portuguese electrical grid as phenomenon that stemmed from (and sheds light on) the construction of the technological landscapes of the Estado Novo (New State) regime (1933-74). Among the many cases of submerged villages recorded in this period, only two have been the subject of research so far: Vilarinho da Furna and Luz, submerged in 1972 and 2002, respectively. However, dam-induced displacement spanned most of the twentieth century, peaking in the 1950s after the state began to actively participate in the construction of the national electric grid, through Law n.º 2002 (1944). Borrowing from Cernea’s “Impoverishment Risks and Reconstruction” model to analyse archival sources and read them along and against the grain, I focus on Portuguese episodes of “Dam-Induced Displacement and Resettlement” to spotlight both how “those who were in the way of progress” acted upon the prospect of displacement and how they were acknowledged—by the companies, by the State—in the shaping of the Portuguese hydroelectric landscapes— through the articulation of programs for internal colonization, the renewal of rural housing or the revision of policies regarding expropriation.